Partly systematic Luby transform codes based on improved progressive edge-growth algorithm for Mars communications. Issue 3 (September 2018) - Wang, Lina; Zhang, Hang; Li, Yaoyao; An, Tianyu
The Luby transform code is a forward error correction code and was originally designed for the erasure channel. In this paper, the Luby transform codes over the Mars communication channel are investigated. To guarantee the reliable data transmission over the Mars communication channel which are usually affected by fading and noises, the progressive edge-growth algorithm is improved and used in for encoding the Luby transform codes. And then a partly systematic Luby transform code with an improved progressive edge-growth algorithm is designed to improve the error propagation phenomenon in Mars communications. Performance evaluations of the designed partly systematic Luby transform code based on the random graph, PEG and improved progressive edge-growth algorithms, respectively, are conducted through a series of simulations. Simulation results show that the performance of the partly systematic Luby transform code based on the improved progressive edge-growth algorithm outperforms those of the partly systematic Luby transform code based on two other algorithms and has the lower bit error rate and overhead.